Maluku's Dominance of Small Islands, Its Challenges, and the Role of Geography Graduates from Pattimura University in Providing Solutions - Salakory, Melianus (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
The management of small islands in border areas, especially those bordering neighboring countries, is carried out to maintain the integrity of the Republic of Indonesia, safeguard national defense and security, improve the welfare of local communities, and develop business opportunities through bilateral cooperation. Another urgent consideration is the complex biogeophysical characteristics of small islands. As mentioned by Agus Dermawan in his presentation, these biogeophysical characteristics include: a) Being separated from the mainland, making them insular; b) Lacking a hinterland and being close to the coast; c) Unable to influence marine hydroclimate; d) Having small catchment areas; e) Limited freshwater sources, catchment areas, and food crops; f) The existence of small islands is influenced by coral reef ecosystems, mangrove forests, and seagrass beds; g) They are highly vulnerable to climate change, both natural and human-induced. Addressing the challenges of coastal areas and small islands from a geographical approach involves the availability of fast, accurate, and objective data. Data is crucial in determining the direction and strategy of policies in the planning, implementation, and evaluation of comprehensive development, particularly for small islands. To meet these needs, the Geography Education Program at Pattimura University and its graduates, including stakeholders, can prioritize several career and policy fields in the era of Industry 4.0, digital transformation, and Society 5.0. These fields include: 1. Satellite imagery and remote sensing analysis; 2. Map production: remote sensing results and satellite image processing; 3. Urban spatial planning analysts, planners, and surveyors; 4. Transportation sector analysts and workers; 5. Edupreneurship; 6. Environmental management; 7. Private sector roles; 8. Disaster management; 9. Tour guides; 10. Environmental destination journalism